May 9 people power saves Malaysia Mahathir leads the way : GE14 votes out corruption - Krishnamoorthy Muthaly 1949- (Krishnamoorthy Muthaly, 2018)
This book is a fascinating read that is retold through the inner stirrings of a young boy, an unfortunate victim of a "business as usual" corrupt system that poses a serious threat to the nation's economy...Through a compelling compilation of observations from journalists, commentators and political activists, veteran journalist and academic Krishnamoorthy sheds penetrating insights into the events leading to the iconic moment when the country's longest ruling Prime Minister, Tun Dr Mahathir Mohamad, saw it as a call of duty to restore the nation's glory. At age 93, he saved the country from the pits of kleptocracy.